Gene structure of nuclear lamin LIII of Xenopus laevis; a model for the evolution of IF proteins from a lamin-like ancestor. - Döring, V (1990)
The lamin LIII gene of Xenopus laevis has been characterized. The gene is duplicated in the Xenopus genome. The transcribed region spreads over 22 kb of genomic DNA encoding 12 exons. Two alternatively spliced mRNAs are observed which encode LIII isoforms that differ only by the 12 C-terminal amino acids which, however, both contain the CaaX motif known to be the target of post-translational modifications. The intron pattern of the lamin LIII gene is strikingly similar to that of an invertebrate intermediate filament (IF) gene over the entire protein coding sequence. The similarity in gene structure is restricted to the rod domain when compared with vertebrate types I-III IF genes. Our data suggest a model of how IF proteins evolved from a lamin-like ancestor by deletion of two signal sequences; the nuclear localization signal and the C-terminal ras-related CaaX motif. The data rule out the previously proposed hypothesis that IF proteins evolved from an intronless ancestor with an early divergence of neuronal and non-neuronal IF proteins. Together with the data presented in the accompanying paper by Dodemond et al. it can be concluded that the tail domains of lamins and invertebrate IF proteins, but not those of vertebrate IF proteins, are homologous. Thus, the different vertebrate IF proteins probably evolved by combination of the central rod domain with different tail domains by exon shuffling.